Penerapan Ruang Terbuka Hijau Di Kota Bandar Lampung - Darra Ananda; Vandan Wiliyanti; Roby Rakhmadi (Jurnal Terekam Jejak, 2024)
The application of Green Open Space in Bandar Lampung is a challenge for the city government in implementing sustainable development. To be sustainable, the portion of Green Open Space must meet the provisions. The city government of Bandar Lampung is trying to fulfill the Green Open Space while carrying out development. Sustainable development will create a sustainable environment so that it will benefit all parties. This study will discuss the efforts of the city government in implementing various aspects of Green Open Space and also the actions taken to maintain ecological sustainability in the city of Bandar Lampung.